2023
DOI: 10.1039/d3ay01627g
|View full text |Cite
|
Sign up to set email alerts
|

Precise temperature control and rapid heating/cooling of infrared spectroscopy samples with a two-stage thermoelectric device

Robert L. White

Abstract: The design and performance of an apparatus for heating and cooling samples during variable temperature infrared spectroscopy studies are described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…The apparatus and methodologies employed for temperature step infrared spectrum measurements are described in detail elsewhere [30,34]. The infrared spectrophotometer was purged with dry air to reduce spectral artifacts caused by fluctuations in water vapor concentration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The apparatus and methodologies employed for temperature step infrared spectrum measurements are described in detail elsewhere [30,34]. The infrared spectrophotometer was purged with dry air to reduce spectral artifacts caused by fluctuations in water vapor concentration.…”
Section: Methodsmentioning
confidence: 99%
“…0.3% RH during infrared spectrum measurements. Previous benchmark studies revealed the importance of good thermal contact between solid samples and the bottom of the button sample holder to achieve accurate temperature measurements [30]. For this reason, samples were deposited in the button sample holder as water slurries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation